2023
DOI: 10.1093/jas/skad214
|View full text |Cite
|
Sign up to set email alerts
|

Integrating sperm cell transcriptome and seminal plasma metabolome to analyze the molecular regulatory mechanism of sperm motility in Holstein stud bulls

Abstract: Considering that artificial insemination is the most widely used assisted reproductive technique in the dairy industry, the semen quality of bulls is very important for selecting excellent stud bulls. Sperm motility is one of the important traits of semen quality, and related genes may be regulated by environmental factors. Seminal plasma can affect sperm cell transcriptome and further affect sperm motility through exosome or other processes. However, the molecular regulation mechanism of bull sperm motility h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
0
0
Order By: Relevance
“…70 Li et al revealed that phenylalanine, tyrosine, and tryptophan biosynthesis and arginine and proline metabolism pathways play an important role in the sperm motility of Holstein bulls. 71 Joint analysis of proteins and metabolites was conducted to identify important metabolic pathways. The most significant pathway was alanine, aspartate, and glutamate metabolism, involving pyruvate, fumarate, GABA, and IL4I1 protein.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…70 Li et al revealed that phenylalanine, tyrosine, and tryptophan biosynthesis and arginine and proline metabolism pathways play an important role in the sperm motility of Holstein bulls. 71 Joint analysis of proteins and metabolites was conducted to identify important metabolic pathways. The most significant pathway was alanine, aspartate, and glutamate metabolism, involving pyruvate, fumarate, GABA, and IL4I1 protein.…”
Section: ■ Discussionmentioning
confidence: 99%
“…For example, Xu et al found that “alanine, aspartate and glutamate metabolism” and “phenylalanine, tyrosine and tryptophan biosynthesis” played an important role in sperm freezability of goat . Li et al revealed that phenylalanine, tyrosine, and tryptophan biosynthesis and arginine and proline metabolism pathways play an important role in the sperm motility of Holstein bulls …”
Section: Discussionmentioning
confidence: 99%